The Government of Carlos E. Restrepo, 1910 -1914. The rise and fall of the Republican Union - Monroy Hernández, Claudia Liliana (Universidad Pedagógica y Tecnológica de Colombia, 2022)
The Republican Union was a political movement that existed in Colombia between 1908 and 1914 and which represented an advance in terms of political modernity under the principlesof tolerance and conciliation. The objective of this article is to analyse the presidential term of Carlos E. Restrepo 1910-1914, considered to be moderate, which sought to consolidate peace andnational progress, confronting economic and political instability and conflicts between conservatives and liberals. The text is framed within political history and attempts to make an account of theinstitutions, subjects, ideas, information networks, the role of the actors and the political practices. The hypothesis that is put forward in this article is that the Republican Union, despite proposing aquick advance in economic progress, formulating a novel policy of public instruction, attempting to separate the Church from politics, and representing both liberals and conservatives in thegovernment of Carlos E. Restrepo, was not solid enough, nor could it confront the traditionalist mentality and political practices of Colombian society at the beginning of the 20th Century that propelled the bipartisan conflict, causing opposition between old friends and allies of republicanism. This resulted in the return of many of its leaders to their parties of origin, the weakening of the republican project and the erosion of the Republican Union as a bipartisan political movement.